Examining the role of job resources on work engagement in the academic setting - Alzyoud, Adel A. Y.; Othman, Siti Zubaidah; Mohd Isa, Mohd Faizal (Canadian Center of Science and Education, 2015)
The aim of this study is to examine the relationship between job resources, namely autonomy, social support and performance feedback and work engagement.Data were gathered through questionnaire from a sample of academicians (n = 532) who worked in four public universities (Mu’tah University, The University of Jordan, The Hashemite University and Yarmouk University) located in the southern, middle and northern region of Jordan.Results indicate that autonomy, social support and performance feedback were a significant factor in influencing academicians work engagement.These findings generally supported past findings, which suggested that employees are more likely to engage with their work if they are given the autonomy, social support and performance feedback.The findings were discussed and implications were also put forward.